Sarawak State Election 2011: survey of voters' behaviour in BN critical areas of Padungan, N10 Pending, N24 Beting Maro, N26 Bukit Begunan, N28 Engkelili and N30 Saribas / Chai Shin Yi … [et.al.] - Chai, Shin Yi; Abang Spawi, Abang Yusuf; Jugah, Ivy (2012)
The Sarawak State Election (hereon after SSE2011) has proved to be one of the most exciting and intense elections the country has seen. Results from the 2006 Sarawak State Election (hereon after SSE 2006) and the 2008 12th General Elections (hereon after GE 2008) have been alarming with the opposition parties increasing their seats in both the state and national level. Although the Barisan Nasional (BN) managed to retain its two-thirds majority seats (55 out of 71) during SSE2011 (Refer Table 1), it was still considered a major loss. This is evident when the opposition managed to increase their seats in the state legislative assembly from two in 2001 and then nine in 2006 to 16 in 2011. This clearly indicated a change in voting loyalty among the voters in Sarawak.